Overestimation of Mangroves Deterioration From Sea Level Rise in Tropical Deltas - Zhijun Dai; Chuqi Long; Xuefei Mei; Sergio Fagherazzi; Yuan Xiong (Geophysical Research Letters, 2024)
Abstract Mangrove forests are critical coastal ecosystems that provide great socio‐ecological services, which are also highly vulnerable to climate change, particularly to sea level rise (SLR). Here we assess changes in mangrove forests in four distinct river/tide/wave‐dominant large deltas along the Indo‐Pacific coast based on 1,336 remote sensing images by machine learning techniques. We find that mangroves are migrating seaward at a rate of 18% ± 12% m/yr, which can offset landward mangroves loss, 67% of which caused by land use conversion. The fact that mangroves are expanding seaward with accretion rates exceeding SLR suggests that climate change has not yet triggered substantial loss in deltaic mangrove forests. Assuming that present environmental conditions do not change and that sediment and organic deposition in the deltaic topsets match SLR rates, we project that 90% of deltaic mangrove forests may start to retreat after 132–194 years. Early inundation of mangroves will occur in wave‐dominated delta.